Analysis of Interim Financial Reports and its Importance to Users in Accordance with International Accounting Standard (34( (An Applied Study at Sumer Commercial Bank) - Hasanain Hameed Majeed; Noor Abdul Razzaq Abdullah (Journal of Madenat Alelem University College, 2021)
The research included the definition of interim financial reports prepared by companies listed in the Iraqi market for securities and the importance of analyzing these reports to compare the results of the analysis using financial analysis ratios for different periods, in a way that provides information for users to make decisions. The published interim financial reports of Sumer Commercial Bank were analyzed using financial analysis indicators to provide more detailed and appropriate information for decision-making in order to enhance the work of the bank. Interim financial reporting and dissemination of awareness to users of the importance of information contained in the interim financial reports as one of the most important sources of information for decision-making and the bank sample research did not prepare interim financial reports in light of the requirements of IAS 34, as well as the absence of local accounting standards in Iraq that define the general framework and requirements for the preparation of interim financial reports.